(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Sustained release microspheres of Lornoxicam were prepared by emulsion solvent evaporation method using ethyl cellulose as release retarding agent and evaluated for in-vivo efficacy and stability study. The anti-inflammatory and analgesic activity of microspheres was evaluated by using the carrageenan-induced hind paw edema and Eddy’s hot plate methods, respectively. In-vivo study of microspheres demonstrated significant analgesic and anti-inflammatory activities of prepared microspheres for a longer period of time as compared to the standard drug. The microspheres showed minor changes (non significant) in physical appearance, particle size with no appreciable change in drug content in different conditions of stability studies. Results also showed that no remarkable changes in the drug release from microspheres formulation of different storage conditions. From these findings, it is concluded that Lornoxicam significantly increases anti-inflammatory and analgesic effect when oral administration in ethyl cellulose microspheres formulation.